2012
DOI: 10.1111/mmi.12118
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a periplasmic trilactone esterase, Cee, revealed unique features of ferric enterobactin acquisition in Campylobacter

Abstract: Summary Ferric enterobactin (FeEnt) acquisition is a highly efficient and conserved iron scavenging system in Gram-negative bacteria. Recently, we have characterized two FeEnt receptors (CfrA and CfrB) in Campylobacter jejuni and C. coli, the enteric human pathogens that do not produce any siderophores. In this study, whole genome sequencing and comparative genomic analysis identified a unique Ent trilactone esterase Cee (Cj1376) in C. jejuni. Genomic analysis and biochemical assay strongly suggested that Cee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 51 publications
(109 reference statements)
1
47
0
Order By: Relevance
“…As a result, the Fe(III) complex of enterobactin is retarded in the periplasm where it is exposed to esterase-catalyzed hydrolysis to its linear components. Because it has been reported that C. jejuni can use bisDHBS 5− as a siderophore independently of enterobactin (10) and the discovery of the trilactone esterase Cee in the periplasm of C. jejuni (25), it appears that CeuE, previously considered to be a [Fe(ENT)] 3− binding protein, is instead adapted to preferentially bind [Fe(bisDHBS)] 2− . This ability to use the enterobactin hydrolysis product for Fe(III) uptake and hence to avoid the metabolic costs of siderophore production provides C. jejuni with a competitive advantage when it encounters enterobactin-secreting bacteria either within the host or contaminated water.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the Fe(III) complex of enterobactin is retarded in the periplasm where it is exposed to esterase-catalyzed hydrolysis to its linear components. Because it has been reported that C. jejuni can use bisDHBS 5− as a siderophore independently of enterobactin (10) and the discovery of the trilactone esterase Cee in the periplasm of C. jejuni (25), it appears that CeuE, previously considered to be a [Fe(ENT)] 3− binding protein, is instead adapted to preferentially bind [Fe(bisDHBS)] 2− . This ability to use the enterobactin hydrolysis product for Fe(III) uptake and hence to avoid the metabolic costs of siderophore production provides C. jejuni with a competitive advantage when it encounters enterobactin-secreting bacteria either within the host or contaminated water.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the esterase Cee and in particular the observation that bisDHBS 5− can be used independently of enterobactin (25) raise important questions about the siderophore preference of the PBP CeuE and its role in the iron uptake in C. jejuni. By using siderophore mimics, we previously demonstrated that CeuE can bind the Fe(III) complexes of both hexadentate and tetradentate catecholate ligands (26,27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1)17. Indeed, the periplasmic enterobactin esterase Cee has been shown to play an important role in the uptake of Fe(III) in C. jejuni , since it hydrolyzes the enterobactin backbone in the periplasm followed by the import of Fe(III)-enterobactin fragment complexes, including bis(2,3-dihydroxybenzoyl-L-Ser), into the cytoplasm18. The observation that there is no known cytoplasmic enterobactin esterase in C. jejuni suggests that hexadentate analogues may first require cleavage to their tetradentate counterparts before transportation into the cytoplasm18.…”
mentioning
confidence: 99%
“…C. jejuni has been shown to acquire iron through enterobactin, hemin, transferrin/lactoferrin and through ferrous ion import [2126]. Iron acquisition has also been demonstrated to be an important colonization and virulence determinant in C. jejuni [21, 22, 27]. Although C. jejuni is unable to synthesize siderophores such as enterobactin, it is able to utilize exogenous enterobactin as an iron source through the action of the CfrA or CfrB transporters [21, 2527].…”
Section: Introductionmentioning
confidence: 99%